A comparison of proliferation levels in normal skin, physiological scar and keloid tissue. Issue 1 (28th February 2023) - Zhang, Ming-Zi; Dong, Xin-Hang; Zhang, Wen-Chao; Li, Ming; Si, Lou-Bin; Liu, Yi-Fang; Li, Hao-Ran; Zhao, Peng-Xiang; Liu, Meng-Yu; Adzavon, Yao Mawulikplimi; Wang, Xiao-Jun; Long, Xiao; et al.
Abstract: Proliferation is an important characteristic of life, and many signaling pathways participate in this complicated process. The MAPK/Erk pathway is a classic pathway in cell proliferation. In this study, expression levels of key factors in the MAPK/Erk pathway were measured to assess the proliferation level among normal skin, physiological scar, and keloid tissue. Thirty patients were selected randomly from the Department of Plastic Surgery at Peking Union Medical College Hospital from January 2019 to December 2020. Histological appearance and fiber tissue content were observed by Hematoxylin and eosin staining and Masson staining. Expression levels of key factors in the MAPK/Erk pathway (ATF2, c-Jun, c-Myc, p38 and STAT1) and relative proteins (HIF-1α and PCNA) in tissues were detected by immunohistochemistry and analyzed as the percentage of positively stained cells in both the tissue epidermis and dermis. Western blot was used for quantitative analysis of the above factors. In results, keloid tissue showed a significantly higher fiber and less cell content. In the immunohistochemical result, higher expression of key factors was observed in the epidermis than in the dermal layer, and the expression of all factors was increased remarkably in keloid tissue. In western blot analysis, all factors (except STAT1) showed higher expression in keloid tissue. In our former research, keloid showed similar apoptosis level as physiological scar and normal skin. On combining our former conclusion and results in this study, an imbalance condition between the high proliferation level and normal apoptosis level may lead to the growth characteristics of keloid.